STATISTICAL STUDY OF LABOR MOVEMENT IN NEW UZBEKISTAN - Akbarova Zaripa (Web of Journals Publishing, 2025)
The labor market in the new Uzbekistan has undergone significant changes in recent years. These changes are mainly associated with economic reforms, state programs, and the expansion of international cooperation. The work being carried out on the labor market in Uzbekistan is based on a number of socio-economic reforms. These reforms are aimed at modernizing the labor market, creating jobs, providing the working population with professions and qualified specialists, and ensuring economic stability.
Keywords: Labor market, labor force, unemployment, employment, educational programs, economy, labor resources, population well-being, productive employment, social protection.